Murine typhus in a liver transplant recipient: Report of a first case - P. Phatharodom (2018)
© 2015 John Wiley & Sons A/S. Published by John Wiley & Sons Ltd. Zoonoses, especially rickettsial diseases, are rarely reported in solid organ transplant recipients. We report here a case of murine typhus in a 69-year-old liver transplant recipient, who presented with acute febrile illness 5 years post transplantation. Although receiving treatment with broad-spectrum antibiotics, he was still febrile and developed progressive dyspnea. Laboratory results showed elevated transaminases and his chest radiograph revealed bilateral interstitial infiltration. The diagnosis of murine typhus was made by a 4-fold rise in specific Rickettsia typhi antibody, using indirect immunofluorescent assay. He dramatically improved after treatment with doxycycline for 7 days. To our knowledge, this is the first case report of murine typhus in a liver transplant recipient.